2022
DOI: 10.1186/s12886-022-02627-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening for novel risk factors related to high myopia using machine learning

Abstract: Background High myopia-related complications have become a major cause of irreversible vision loss. Evaluating the association between potential factors and high myopia can provide insights into pathophysiologic mechanisms and further intervention targets for myopia progression. Method Participants aged 12–25 years from National Health and Nutrition Examination Survey 2001–2006 were selected for the analysis. Myopia was defined as spherical equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Vitamin A itself is not the main biologically active intermediary of its functions. As previously mentioned, all-trans retinoic acid (atRA) and 11-cis retinaldehyde are critical regulators of gene transcription related to vitamin A’s functions [ 33 ]. Evidence from GWAS studies suggested that retinoic acid metabolism genes contribute to susceptibility to refractive errors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A itself is not the main biologically active intermediary of its functions. As previously mentioned, all-trans retinoic acid (atRA) and 11-cis retinaldehyde are critical regulators of gene transcription related to vitamin A’s functions [ 33 ]. Evidence from GWAS studies suggested that retinoic acid metabolism genes contribute to susceptibility to refractive errors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that no cycloplegic agent was used in measuring refractive errors, this more conservative definition of myopia was employed to avoid misclassification of myopia. In this study, myopia was defined as an SER value ≤−1.0 diopter (D), and high myopia was defined as an SER value ≤−5.0 D. Participants were divided into three groups: normal vision (SER > −1.0), low myopia (SER ≤ −1.0), and high myopia (SER ≤ −5.0 D) (16). interview was conducted 3-10 days after the first one via a phone call.…”
Section: N-3 Pufa Measurement and The Definition Of Myopiamentioning
confidence: 99%